Henry James’s The Portrait of a Lady (1881) or Jane Campion’s 1996 movie adaptation? - Eren, Buse (Journal of History Culture and Art Research, 2015)
Henry James’s The Portrait of a Lady (1881) or Jane Campion’s 1996 movie adaptation? Abstract This paper aims at identifying both the similarities and differences between Henry James’s novel “The Portrait of a Lady” (1881) and Jane Campion’s 1996 movie version. We will try to answer the following questions: Is a Modernist literary piece still appealing to the 21st century readers? What is lost and what is gained from the screen adaptation of the book? Would a person reading the novel be interested in watching the movie and vice versa? Last but not least, we will compare the portrayal of the characters in the novel and their materialization in the movie through the parts of Nicole Kidman, John Malkovich, Barbara Hershey and Mary Lauise Parker.